Meta-Analysis: Risk Factors Associated with Multidrugs-Resistant Tuberculosis (MDR-TB) in Tuberculosis Patients - Nurul Dwi Andriani; Resta Dwi Yuliani (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Today, the world not only has to face a higher number of deaths from TB every year, but other challenges arise in the form of drug-resistant TB with risk factors that can affect the incidence of MDR TB, namely treatment-related factors (direct) and other factors (not direct). direct) such as biological, social, economic, and health system factors. The aim of this study was to estimate the risk of HIV infection, smoking and previous medication history on the incidence of MDR TB, with a meta-analysis of primary studies conducted by previous authors.Subjects and Method: This study was conducted using a systematic review and meta-analysis study design using PICO, population: Tuberculosis Patients. Intervention: Risk Factors for HIV Infection, Smoking, and History of Medication. Comparison: no HIV infection, no smoking and no history of medication, Outcome: MDR-TB incidence. The articles used in this study came from 4 databases, namely Pubmed, ScienceDirect, ProQuest and Google scholar. The article keywords are (